Gene family analysis of the Arabidopsis pollen transcriptome reveals biological implications for cell growth, division control and gene expression regulation - Pina, C. (2005)
Upon germination, pollen forms a tube that elongates dramatically through female tissues to reach and fertilize ovules. While essential for the life cycle of higher plants, the genetic basis underlying most of the process is not well understood. We previously used a combination of flow cytometry sorting of viable hydrated pollen grains and GeneChip array analysis of onethird of the Arabidopsis (Arabidopsis thaliana) genome to define a first overview of the pollen transcriptome. We now extend that study to approximately 80% of the genome of Arabidopsis by using Affymetrix Arabidopsis ATH1 arrays and perform comparative analysis of gene family and gene ontology representation in the transcriptome of pollen and vegetative tissues. Pollen grains have a smaller and overall unique transcriptome (6,587 genes expressed) with greater proportions of selectively expressed (11%) and enriched (26%) genes than any vegetative tissue. Relative gene ontology category representations in pollen and vegetative tissues reveal a functional skew of the pollen transcriptome toward signaling, vesicle transport, and the cytoskeleton, suggestive of a commitment to germination and tube growth. Cell cycle analysis reveals an accumulation of G2/Massociated factors that may play a role in the first mitotic division of the zygote. Despite the relative underrepresentation of transcription-associated transcripts, nonclassical MADS box genes emerge as a class with putative unique roles in pollen. The singularity of gene expression control in mature pollen grains is further highlighted by the apparent absence of small RNA pathway components.